PEMBEKALAN ETOS KERJA & BUDAYA KERJA MELENGKAPI KOMPETENSI PENDIDIKAN JALUR VOKASIONAL - M.Budi Kuntjoro; Nunuk Praptiningsih; Rustomo (Politeknik Penerbangan Indonesia Curug)
Vocational education, Indonesia plans to build more vocational schools to cater to the growing labour market for skill worker, particularly in transportations sector, agriculture, fisheries and animal industry, also another private sectors. Refer to Undang Undang. No. 20 Tahun 2003 tentang Sistem Pendidikan Nasional and Peraturan Pemeritah No. 17 Tahun 2010 tentang Pengelolaan dan Penyelenggaraan Pendidikan. In Indonesia, Education system is divided between vocational path, academic path and professional path. A vocational school, sometimes called vocational college Vocational college are traditionally focus on job-specific training, who are typically bound for one of skill, rather than providing academic training for pursuing careers in a professional dicipline. Vocational education cover program of diploma 1, diploma 2, diploma 3 and diploma 4. After attend the lecture get title : Ahli Pratama (AP); Ahli Muda (A.Ma); Ahli Madya A.Md) and Sarjana Sain Terapan (S.SiT). Vocational education, hard skill of motoric are obliged to become curriculum in the form of Iesson of functional skill. Another side efficiency of motoric through subject of market oriented approach. Generally, vocational education system of in Indonesia had not balance yet between hard skill with personality attitude ( soft skill). Almost company in this time, need human resource having prime technical skill, ready for use and good personality attitutde.